PELAKSANAAN ZOOM MEETING SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN JASMANI KESEHATAN DAN REKRESAI SECARA DARING KELAS IX MTS NURUL YAQIN PEKANBARU - Syahrin Saputra; Zainur Zainur; Syahriadi Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the government policy that requires all educational institutions across Indonesia to conduct online education and learning activities due to the Covid-19 outbreak, while physical education classes are a class that requires students to do more physical activity or exercise then study theory like any other general subject. The aim of this research was to determine the implementation and effectiveness of the media zoom meeting as a medium for online learning of physical education, health and recreation. The sampling technique was targeted sampling on 28 deaf students. The instrument used in this research is the use of a questionnaire and interviews with teachers and students. Based on the results of the above survey, it can be seen that the implementation of the zoom meeting as a medium of learning physical education, health and online recreation for class IX MTs Nurul Yaqin Pekanbaru is explained in three indicators, namely, the learning planning indicator has a high or good interpretation or 79.67%. On the indicators of the learning process with sufficient interpretation or equal to 60.71%. On the indicators of learning evaluation with sufficient interpretation or equal to 68.86%. If it is concluded that the implementation of zoom meeting learning at MT's Nurul Yaqin gets a good category with a percentage of 82.86%.Key Words: Zoom Meeting, Learning Media, PJOK